2016
DOI: 10.1016/j.jns.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Loss of extra-striatal phosphodiesterase 10A expression in early premanifest Huntington's disease gene carriers

Abstract: Huntington's disease (HD) is a monogenic neurodegenerative disorder with an underlying pathology involving the toxic effect of mutant huntingtin protein primarily in striatal and cortical neurons. Phosphodiesterase 10A (PDE10A) regulates intracellular signalling cascades, thus having a key role in promoting neuronal survival. Using positron emission tomography (PET) with [(11)C]IMA107, we investigated the in vivo extra-striatal expression of PDE10A in 12 early premanifest HD gene carriers. Image processing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Recently, our group investigated PDE10A expression using PET with [ 11 C]IMA107 in 12 far-onset premanifest HDGECs who were on average 25 years from predicted symptomatic onset, clinically normal and had no volumetric brain changes as confirmed by MRI voxel-based morphometry and FreeSurfer volumetric analysis ( 83 , 84 ). Striatal and pallidal [ 11 C]IMA107 binding was reduced by 25–33%, and a 35% increase in binding was observed in the motor thalamic nuclei in premanifest HDGECs compared to HC ( 83 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our group investigated PDE10A expression using PET with [ 11 C]IMA107 in 12 far-onset premanifest HDGECs who were on average 25 years from predicted symptomatic onset, clinically normal and had no volumetric brain changes as confirmed by MRI voxel-based morphometry and FreeSurfer volumetric analysis ( 83 , 84 ). Striatal and pallidal [ 11 C]IMA107 binding was reduced by 25–33%, and a 35% increase in binding was observed in the motor thalamic nuclei in premanifest HDGECs compared to HC ( 83 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous PET studies have shown that PDE10A expression decreased in the striatum and pallidum and increased in the motor thalamus of premanifest HD gene carriers compared to matched healthy controls [135]. PET imaging research using [ 11 C] IMA107 demonstrated a 25%–33% reduction in striatal PDE10A 25 years earlier than predicted symptomatic onset [135,136]. Decreased PDE10A expression was mostly restricted to the dorsal sensorimotor striatum [135], and lower striatal PDE10A expression was associated with disease burden and severity [137].…”
Section: Striatal Pathologymentioning
confidence: 99%
“…In a study of a transgenic rodent model of HD, preferential loss of striosomal neurons was reported [224]. Moreover, a PET study of early premanifest HD gene carriers revealed that extra-striatal PDE10A expression decreased by 25% and 50% in the insular cortex and occipital fusiform gyrus, respectively [136]. These cortical areas are associated with cognitive and limbic functions and are striosome-related areas [225].…”
Section: Striatal Pathologymentioning
confidence: 99%
“…Currently, PDE10 is considered a promising target for CNS diseases, especially schizophrenia and Huntington's disease (HD). Although numerous studies have reported that PDE10A expression in the striatum and different other brain regions of post-mortem HD patients [113][114][115] and HD animal models [113,116] is reduced, inhibition of PDE10A has shown rescue of behavioral, neurodegenerative, and electrophysiological deficits in HD animal models.…”
Section: Phosphodiesterase 10 Inhibitorsmentioning
confidence: 99%